THE EFFECTIVENESS OF THE RADON TRANSFORM AGAINST THE QUANTIZATION NOISE - Cherifi, Mehdi; Lahdir, Mourad; Ameur, Soltane; Ameur, Zohra (European Scientific Journal, ESJ, 2015)
The aim of image compression consists to reduce the number of bits required to represent an image. The Radon transform has become a very interesting tool in the field of image processing. Its Robustness against noises such as white noise has boosted the researchers to realize methods of detection of objects in noisy images. The Discrete Cosine Transform has shown its efficacy in the energy compaction of the image to be compressed into a smaller number of coefficients. It is part of many international standards including JPEG and MPEG. In this paper, we present an image compression method, which is the modification of the scheme presented by Predeep and Manavalan. The modification consists to use a high scale quantization, which is 20 in order to realize a heavy quantization for the DCT to achieve a high compression. A comparative study is performed to show the contribution of this modification.